Dilemmas of growth in prewar Japan - Morley, James William, 1921-; Beckmann, George M. (Princeton University Press, 2015)
The sixth and final volume in the series published for the Conference on Modern Japan reviews the political, economic and foreign policy problems faced by Japan during the 1930's and '40's. James Morley's introductory chapter, "Choice and Consequence," and Edwin O. Reisehauer's conclusion. "What Went Wrong?" define the context of the discussion. Contents: "Foreword," John Whitney Hall. 1. "Introduction: Choice and Consequence," James William Morley. PART ONE: Political and Military. II. "The Bureaucracy as a Political Force, 1920-45," Robert M. Spaulding, Jr. III. "Retrogression in Japan's Foreign Policy Decision-Making Process," Chihiro Hosoya. IV. "The Failure of Military Expansionism," Akira Iriye. V. "The Radical Left and the Failure of Communism," George M. Beekmann. PART TWO: Economic and Social. VI. "Rural Origins of Japanese Fascism," R.P. Dore and Tsutomu Ouchi. VII. "The Economic Muddle of the 192O's," Hugh I. Patrick. VIII. "Big Business and Politics in Prewar Japan," Arthur E. Tiedemann. PAKT THREE: Intellectual. IX. "Intellectuals as Visionaries of the New Asian Order," James B. Crowley. X. "Nakano Seigo and the Spirit of the Meiji Restoration in Twentieth- Century Japan," Tetsuo Najita. XI. "Oyama Ikuo and the Search for Democracy," Peter Duus. PART FOUR: Comparisons and Conclusions. XII. "Japan and Germany in the Interwar Period," Kentaro Hayashi. XIII. "What Went Wrong?" Edwin O. Reischauer. Index. Originally published in 1974. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905